2020
DOI: 10.35188/unu-wider/2020/875-7
|View full text |Cite
|
Sign up to set email alerts
|

Roots of dissent: Trade liberalization and the rise of populism in Brazil

Abstract: Typescript prepared by Siméon Rapin. United Nations University World Institute for Development Economics Research provides economic analysis and policy advice with the aim of promoting sustainable and equitable development. The Institute began operations in 1985 in Helsinki, Finland, as the first research and training centre of the United Nations University. Today it is a unique blend of think tank, research institute, and UN agency-providing a range of services from policy advice to governments as well as fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…For some time, there has been growing concern among scholars and political commentators about the political consequences of rises in inequality in the USA since the 1980s-and in many other parts of the world (Piketty 2014). Studies have shown evidence for links between increases in inequality and unprecedented rises in far-right and populist political parties, the election of several governments with strong nationalistic overtones (including in the USA), and the erosion of democratic institutions (Hacker 2006;Piketty 2014;Rodrik, 2018;Algan et al 2017;Iacoella et al 2020). Our results indicate that US counties with initially high levels of economic (and racial) inequality were in fact more likely to protest during the COVID-19 pandemic against government policies that further deteriorated their economic standing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some time, there has been growing concern among scholars and political commentators about the political consequences of rises in inequality in the USA since the 1980s-and in many other parts of the world (Piketty 2014). Studies have shown evidence for links between increases in inequality and unprecedented rises in far-right and populist political parties, the election of several governments with strong nationalistic overtones (including in the USA), and the erosion of democratic institutions (Hacker 2006;Piketty 2014;Rodrik, 2018;Algan et al 2017;Iacoella et al 2020). Our results indicate that US counties with initially high levels of economic (and racial) inequality were in fact more likely to protest during the COVID-19 pandemic against government policies that further deteriorated their economic standing.…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing literature, shocks like the COVID-19 pandemic may magnify economic inequalities and lead to protests due to changes in economic conditions or due to changes in political and social preferences (Enos et al 2019;Rozenas and Zhukov 2019;Enikolopov et al 2020). The first mechanism-the deterioration of economic prospects-has been shown by political scientists, sociologists, and economists to be central to social mobilization, protests, and civil unrest (Gurr 1970;Boix 2008;Verwimp et al 2019;Iacoella et al 2020;Ponticelli and Voth 2020). There is a growing consensus that the COVID-19 pandemic will lead the global economy into the worst recession since the Great Depression (IMF 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Also, industrial decline may have political consequences. Research done in Brazil (Iacoella et al, 2020) found that the zones most negatively affected by trade liberalization in the 1990s were the most likely to vote for Jair Bolsonaro. Still, beyond these traits, there are others of a more structural nature that can also be thought to explain the evolution of the bilateral relationship.…”
Section: Testing Three Explanationsmentioning
confidence: 99%
“…For populism experts such as Cas Mudde and Rovira Kaltwasser (2017), populism is a crisis of weak or weakening liberal institutions and populist majoritarianism emerges as a kind of mutation of liberal democracy because of institutional weakness. Mainstream and heterodox economists alike have produced longitudinal and empirical studies correlating the rise of populism with negative impacts of free trade on workers and small businesses (Grossman, 2020;Iacoella et al, 2020;Rodrik, 2018).…”
Section: Chapter Two: Theorizing Right-wing Populism and Crisis Of Neoliberal Accumulationmentioning
confidence: 99%
“…On the other hand, some recent literature also looks at economic "stresses" (Guriev & Papaioannou, 2020;Edelman, 2019) as explaining the ontological insecurity driving right-wing populism. These studies show evidence for a correlation between economic changes like austerity, deindustrialization, and trade liberalization as leading to a rise in both right and left-wing populism (Grossman, 2020;Rodrik, 2020;Iacoella et al, 2020). Some longitudinal studies suggest a direct correlation between periods of recession in free trade or liberalized economics with the rise of populism and protectionism as a reaction to increasing impoverishment of certain sectors (Margalit, 2013).…”
Section: Marzalmentioning
confidence: 99%